Arabic Language Learning Model in the Era of Independent Curriculum that is Relevant in the 21st Century / Model Pembelajaran Bahasa Arab di Era Kurikulum Merdeka yang Relevan di Abad Ke-21 - Safina Nurrahma; Candra Suryanto (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
Arabic, which since 1972 has become an international language and is the official language of 25 countries in the world, is increasingly widespread. Arabic language learning continues to develop, both from methods, learning media to the curriculum used. This study aims to determine the models of Arabic language learning in the era of independent curriculum that are relevant in the 21st century. This research uses a descriptive method with a qualitative approach. Data is obtained by literature study (libraby research), namely by collecting, processing, and analyzing data related to the Arabic learning model in the independent curriculum. The result of this study is that there are 5 learning models that are relevant to learning Arabic curriculum Merdeka in the 21st century. Among them are: 1) Project Based Learning (PjBL) Model, 2) Problem Based Learning (PBL) Learning Model, 3) Inquiry Based Learning Model, 4) Discovery Learning Model and 5) Cooperative Learning Model.Abstrak: Bahasa Arab yang sejak 1972 menjadi bahasa internasional dan menjadi bahasa resmi 25 negara di dunia semakin tersebar luas. Pembelajaran bahasa Arab terus berkembang, baik dari metode, media pembelajaran hingga kurikulum yang digunakan. Penelitian ini bertujuan untuk mengetahui model pembelajaran bahasa Arab di era kurikulum merdeka yang relevan di abad ke-21. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Data diperoleh melalui studi literatur (libraby research), yaitu dengan mengumpulkan, mengolah, dan menganalisis data yang berkaitan dengan model pembelajaran bahasa Arab dalam kurikulum mandiri. Hasil penelitian ini adalah terdapat 5 model pembelajaran yang relevan dengan pembelajaran kurikulum bahasa Arab Merdeka di abad ke-21. Diantaranya adalah: 1) Model Project Based Learning (PjBL), 2) Model Problem Based Learning (PBL), 3) Model Inquiry Based Learning, 4) Model Discovery Learning dan 5) Model Cooperative Learning.